Design and performance testing of areca nut thresher machine using solid triangle spike tooth type - R Bulan; None Mustaqimah; K Siregar; S R Lesdiana; K Anwar; A Sitorus (My University, 2021)
Abstract Technology for handling agricultural products from areca nut has received less attention. However, the economic potential of the areca nut is comparable to that of other palm trees. Threshing areca nut from the bunch is one of the procedures that must be completed to obtain high-quality betel nut. Therefore, this research aims to design and test an areca nut threshing machine that uses a solid triangle spike-type threshing tooth. This study uses an experimental manufacturing method in the workshop and laboratory testing. A detailed engineering drawing of areca nut thresher machine is a guide in carrying out the manufacturer. The influence of rotational speed on the threshing shaft (34 rpm, 42 rpm, and 50 rpm) was investigated to determine the machinery’s performance (percentage of threshing results, engine capacity, and fuel consumption). This study indicates that the areca thresher machine has been successfully designed with a diesel motor driving source of 6.5 hp, 2200 rpm. Applied a rotational speed of 50 rpm will give the best percentage of threshing products. The increase in rotational speed applied to the threshing machine will be in line with the rise in the engine capacity. In addition, the fuel consumption of a diesel engine from this thresher machine is 0.039 l/hr.
Keywords: Threshing; Areca; Agricultural Engineering and Mechanization